Search for exotic physics in double-β decays with GERDA Phase II. Issue 12 (1st December 2022) - Agostini, M.; Alexander, A.; Araujo, G.; Bakalyarov, A.M.; Balata, M.; Barabanov, I.; Baudis, L.; Bauer, C.; Belogurov, S.; Bettini, A.; Bezrukov, L.; Biancacci, V.; et al.
Abstract: A search for Beyond the Standard Model double- β decay modes of 76 Ge has been performed with data collected during the Phase II of the GERmanium Detector Array (Gerda ) experiment, located at the Laboratori Nazionali del Gran Sasso of INFN (Italy). Improved limits on the decays involving Majorons have been obtained, compared to previous experiments with 76 Ge, with half-life values on the order of 10 23 yr. For the first time with 76 Ge, limits on Lorentz invariance violation effects in double- β decay have been obtained. The isotropic coefficient åof (3), which embeds Lorentz violation in double- β decay, has been constrained at the order of 10 -6 GeV. We also set the first experimental limits on the search for light exotic fermions in double- β decay, including sterile neutrinos.